Awareness and attitude regarding postnatal care and immunization practice among antenatal mothers - S., Srinivasa; Agrawal, Avinash; M., Madhurya R.; Hiremath, Shrisha (International Journal of Contemporary Pediatrics, 2020)
Background: Under 5 mortality is a key indicator of health status of the country. Optimum care in postnatal period with immunization as per recommended schedule and exclusive breastfeeding with appropriate technology are the most essential factors for optimum growth and development of the child and to prevent under five mortality. The study was done to assess the knowledge and attitude of antenatal mothers on vaccination and postnatal care. Methods: Total 150 pregnant women were required to answer a series of questionnaire related to demographic data, awareness and attitude towards postnatal care, breastfeeding and immunization. Results: Total 90% of the women are aware regarding immunization at birth, 87% of them got the information from a person, who is directly related to health system. Statistically 97.3% mother were aware about importance to keep the baby covered. Every 3 out of 4 women knew that breastfeeding to be started within 1 hour of life. Only 40% were aware that prelacteal feed should never be given to newborns and 74% of the women think that jaundice in newborn requires evaluation. Conclusions: There is a need to educate antenatal mothers about various aspects of immunization and postnatal care including breastfeeding.